2007
DOI: 10.2147/nedt.2007.3.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Ziconotide: a review of its pharmacology and use in the treatment of pain

Abstract: Ziconotide is a powerful analgesic drug that has a unique mechanism of action involving potent and selective block of N-type calcium channels, which control neurotransmission at many synapses. The analgesic efficacy of ziconotide likely results from its ability to interrupt pain signaling at the level of the spinal cord. Ziconotide is a peptidic drug and has been approved for the treatment of severe chronic pain in patients only when administered by the intrathecal route. Importantly, prolonged administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
179
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(187 citation statements)
references
References 110 publications
1
179
0
Order By: Relevance
“…NVDCCs regulate presynaptic release of transmitters at many synapses (Snutch, 2005). The NVDCC blocker ziconotide is a powerful analgesic drug approved for the treatment of severe chronic pain in humans (McGivern 2007), and other NVDCC blockers are being developed for use in humans to treat stroke and pain (Giordanetto et al, 2011). Such blockers might also help treat addiction, since rodent studies have shown that NVDCCs promote alcohol intake (Newton et al, 2004) and that NDVCC blockers are antinociceptive, potentiate morphine analgesia, and attenuate morphine tolerance and physical dependence and withdrawal (Meng et al, 2008).…”
Section: Other Calcium Channel Antagonistsmentioning
confidence: 99%
“…NVDCCs regulate presynaptic release of transmitters at many synapses (Snutch, 2005). The NVDCC blocker ziconotide is a powerful analgesic drug approved for the treatment of severe chronic pain in humans (McGivern 2007), and other NVDCC blockers are being developed for use in humans to treat stroke and pain (Giordanetto et al, 2011). Such blockers might also help treat addiction, since rodent studies have shown that NVDCCs promote alcohol intake (Newton et al, 2004) and that NDVCC blockers are antinociceptive, potentiate morphine analgesia, and attenuate morphine tolerance and physical dependence and withdrawal (Meng et al, 2008).…”
Section: Other Calcium Channel Antagonistsmentioning
confidence: 99%
“…Indeed, inhibition of CaV2.2 by synthetic conopeptides provides analgesic relief in a variety of platforms (3)(4)(5)(6). However, given the importance of CaV2.2 integrity in peripheral and central synapses, directly targeting channel function is complicated by a myriad of adverse side effects (7)(8)(9). Targeting protein-protein interactions that regulate CaV2.2 may provide analgesic benefits similar to those provided by direct inhibition, while avoiding complications associated with channel block.…”
mentioning
confidence: 99%
“…Ziconotide, a natural peptide from snail venom, is approved for the treatment of intractable chronic pain [8,9]. Ziconotide administration is limited to intrathecal because of cardiovascular liabilities caused by the intravenous route [10]. There appears to be many treatments for neuropathic pain, but most of them are not effective in some patients showing high numbers needed to treat (NNT) and/or develop serious side effects (Table 1).…”
Section: Therapeutics For Chronic Neuropathic Painmentioning
confidence: 99%